Survei Keterampilan Passing Bawah Pada Team Bola Voli Putra STKIP Kie Raha Ternate - Mahatma Raison Pribadi (Peneliti.net, 2023)
This research is a descriptive study that describes the ongoing situation or situation without proposing a hypothesis, Suharsimi Arikunto (2006: 32) states that